Modular robot wrist - ROSHEIM; MARK E (1993)
A mechanical joint includes a mechanism for effecting pitch and yaw, the effecting mechanism being attached to a housing support, a yaw drive mechanism slidably engaging the housing support, a pitch drive mechanism slidably engaging the housing support and a mechanism to actuate the yaw drive mechanism and the pitch drive mechanism, In accordance with the present invention, a unitary guide mechanism attached to the housing stabilizes movement of the yaw drive mechanism and the pitch drive mechanism by receiving at least a portion of the yaw drive mechanism and the pitch drive mechanism.